Jabariyah dan Qadariyah dalam Pemikiran Tentang Takdir - Fathur Rohman AR (Pena Islam Jurnal Pendidikan Agama Islam, 2021)
Talking about divinity seems to have no end, no angle and is a universal fact. This is not only found in modern society but also in even the most primitive society. Historical studies of the origins of religion have proved this fact. Therefore, many theologians and religious philosophers attribute the argument of the existence of god to this historical fact. In fact, some of them claim that the phenomenon of divinity has been embedded in human beings as an innate idea so that it has become a solid belief. Qadariyah is the opposite of Jabariyah, that all human actions are not intervened by God. This school holds that each person is the creator of all his actions; he can do something or leave it at his own will.